Validation of a novel 3D printed positioning device and dynamic radiographic technique to quantify rotational laxity of the stifle in dogs - Yu, Jin; Griffon, Dominique J.; Wisser, Gary; Mostafa, Ayman A.; Dong, Fanglong (Frontiers in Veterinary Science, 2023)
Cranial cruciate ligament deficiency (CCLD) results in internal rotational laxity of the stifle (RLS). By contrast, tibial torsion (TT) is an anatomical feature of the tibia along its longitudinal axis. The objective of this study was to validate a dynamic radiographic technique to measure RLS and differentiate it from TT. Models included transection of the CCL for RLS and an osteotomy for TT. One limb within 8 pairs of canine cadaveric hind limbs was randomly assigned to CCLD. The contralateral limb underwent TT, followed by CCLD. Neutral and stress radiographs were taken with the limb in a custom rotating 3-D printed positioning device before and after each modification. The position of the calcaneus on neutral views and the magnitude of its displacement under standardized torque were compared within limbs and between groups. Transection of the CCL increased the magnitude of displacement of the calcaneus by 1.6 mm (0.3-3.1mm, p < 0.05) within limbs. The lateral calcaneal displacement (dS-dN) tended to be greater when CCLD limbs were compared to limbs with intact CCL. A magnitude of calcaneal displacement of 3.45 mm differentiated limbs with RLS from intact limbs with 87.5% sensitivity and 68.7% specificity. The calcaneus was displaced further laterally by about 3mm on neutral radiographs (dN) when limbs with experimental TT were compared to those without TT (p <0.05). A calcaneus located at least 3.25mm from the sulcus differentiated limbs with TT from intact limbs with 87.5% sensitivity and 87.5% specificity. The technique reported here allowed detection of RLS, especially within limbs. A calcaneus located at least 3.25 mm on neutral radiographs of large dogs should prompt a presumptive diagnosis of TT.